Evaluation of recreation-use impacts in relation to physical factors along Gunung Datok Trail, Negeri Sembilan, Malaysia - Jumaat, Noor Jalilah (2013)
As one of the most popular recreational settings in Malaysia, Gunung Datok Recreational Forest has experienced many physical changes along its primary hiking trail, which has been developed for the purpose of mountain climbing. The excessive use of the trail has led to deterioration of soils. In addressing this issue, the aim of this study is to evaluate the recreation-use impacts related to physical factors along Gunung Datok Trail. The present research also attempts to determine the relationships between recreational use and its impacts for the purpose of resource management. A six-month study (July to December 2010) was conducted using an integrated method: track problem assessment method and trail condition classes. Seventeen point samplings were determined using the track problem assessment method where predefined problems were detected based on the expansion of trail width, soil compaction, trail depth, and soil erosion. Subsequently, all the sampling points were categorised using trail condition class survey method. In the first part of this study, the current physical conditions of Gunung Datok Trail were monitored. Measurements of the trail width, depth, compaction, and soil erosion were taken at every point sampling. The study found that the minimum length of trail width was 1.10 meters at point sampling 15, while the widest trail was found at point sampling 3 with a length of 4.70 meters. For trail depth, point sampling 16 was identified as the deepest trail with 1.23 meters, while the shallowest trail was at point sampling 1 with only 0.48 meters. This study discovered that point samplings 1, 6, and 7 had the highest degree of soil compaction with 4.83 g/cm2. Meanwhile, for soil erosion, point sampling 3 accumulated the largest amount of soil loss with 4.63 m2 . Overall, point sampling 3 was identified as the most degraded area, where it showed the most visible changes as compared with the other point samplings. The second part of this study focused on determining the physical factors which contributed significantly to the recreation-use impacts along the trail. Four attributes were selected as the physical factors: slope gradient, soil texture, rainfall intensity and amount of use. Soil texture was identified through particle-size analysis using pipette method, while slope gradient was measured using a clinometer. Data on rainfall intensity and number of visitors for each month of the study were gathered from the Meteorology Department of Malaysia and Gunung Datok Coorperation Berhad respectively. For data analysis, Pearson correlation and regression analysis were used to examine the strength of relationship between the physical factors and recreation-use impacts. The results revealed that soil texture and slope gradient had contribute to the erosion process and expansion of trail. From the regression models, slope gradient was found to be the highest explanatory predictor for soil erosion (R2 = .053), while soil texture showed the highest R2 value for trail width with 4.4%. Nevertheless, both factors were found to be the major predictors for all the recreation-use impact indicators. Even though rainfall and amount of use were not found to significantly influence the impacts, both factors were considered as the supporting factors. In the third part of this study, seventeen point samplings were categorised using trail condition classes. At the end of the study, the results showed that 17.6% (three point samplings) were classified as moderately damaged trail, 64.7% (eleven point samplings) were highly damaged, and three point samplings (17.6%) were detected as hotspot areas. The hotspot areas (point samplings 3, 7, and 14) require immediate mitigation actions to avoid further degradation. Overall, Gunung Datok Trail was categorised as Class III out of four classes, which indicates it is a highly damaged trail. Therefore, the whole trail requires continuous observation and maintenance; priority should be given to the highly damaged areas. In conclusion, Gunung Datok Trail needs immediate mitigation actions, especially in the hotspot areas. Points with steep slope gradient require extra attention from the park management to ensure sufficient preventive measures for users' safety. Besides, a continuous monitoring programme needs to be implemented by the park management to minimise future trail degradation.